Medicine use in swallowing-impaired patients: Pharmacists' knowledge, practice and information needs - Masilamoney, Mehrusha (Rhodes University, Faculty of Pharmacy, Pharmacy, 2018)
Dysphagia, or swallowing impairment, is a growing problem that affects 13.5% of the general population. The ability to swallow is essential for patients taking oral medicines, so this presents a challenge for swallowing-impaired (SI) patients as tablets and capsules will usually require modification prior to ingestion. Pharmacists should play a central role in advising SI patients about their medicine use, as well as problems that may impact on safety, adherence and therapeutic outcome. However, little is known about pharmacists' level of knowledge, their practice and their information needs when dealing with SI patients and their use of medicines. The aim of this study was to investigate pharmacist knowledge, practice and information needs relating to the support of SI patients and their medicine-related needs. The study design included both quantitative and qualitative methods. A quantitative questionnaire was developed to collect data on the knowledge, practice and information needs of pharmacists and was piloted in 10 pharmacists, which resulted in minor modifications. The questionnaire was converted to a web-based survey and emailed to all pharmacists registered with the South African Pharmacy Council. Two knowledge scores were generated by summating correct responses: knowledge of dysphagia (KOD) and knowledge of medicine use (KOMU) in SI patients. Correlation analysis was used to investigate the strength of the relationship between specific variables with KOD and KOMU using the Pearson correlation coefficient. Qualitative semi-structured interviews were conducted with pharmacists from community, hospital and primary healthcare clinics in both a small town and a major metropole. The aim was to gain deeper understanding of issues arising from the survey, and to explore preferences for topic-specific information materials. All interviews were audio-recorded and transcribed verbatim. Thematic analysis was used to analyse the data. A total of 439 pharmacists responded to the survey, with 67% being females.The mean KOD score out of a maximum score of 10 was 6.1 Â± 1.8. KOD was inadequate (<5) in just over one-third (37.8%) of pharmacists. The mean KOMU score achieved (maximum score 17) was 9.4 Â± 2.0, with inadequate knowledge (<10) being established in just over two-thirds of pharmacists (70.8%). Age, length of registration as a pharmacist, and years of practice in a setting with direct patient interaction were significantly but weakly correlated with KOMU, whereas KOD showed no significant association with these variables. Qualification significantly influenced both KOD and KOMU; the highest group with adequate knowledge had either a Masters or a PharmD degree. Fewer than half the pharmacists (44%) never ask patients about their swallowing ability, and most (86%) reported no knowledge of locally available viscosity enhancers. Almost all pharmacists were interested in receiving information materials on assisting SI patients with their medicine use. Three major themes emerged from the semi-structured interviews. Pharmacists recognised their knowledge deficit and felt that lack of both undergraduate training and formal training during practice, as well as limited exposure to SI patients, were contributing factors. Barriers to their practice with SI patients included lack of time, lack of institutional support and lack of easily accessible references on the pharmacists' role in supporting medicine use in SI patients. Lastly, most pharmacists were not prepared to take ownership of medicine-related problems in SI patients and had conflicting opinions of the pharmacists' role, usually shifting the responsibility of medicine use in SI patients to nurses. This is the first study to investigate pharmacist knowledge of medicine use in SI patients. The findings indicate that pharmacists do not have the requisite knowledge when dealing with SI patients and their medicine-taking issues despite being the most highly trained healthcare professionals in this field. Lack of undergraduate training, in-house training and limited exposure to SI patients were reported to contribute to poor knowledge. Current practice revealed that there appears to be poor communication among different healthcare professionals, pharmacists were reluctant to work with and/or train nurses on appropriate medicine use in SI patients, and there appeared to be ambiguity surrounding the role of a pharmacist. This research identified that pharmacists regard this topic to be highly relevant to their everyday practice and are keen to receive more information and training relating to this area of study. Information materials were designed and will be made accessible to all pharmacists registered in South Africa.
Keywords: Deglutition disorders; Drugs -- Administration; Oral medication -- Administration; Pharmacists -- Practice; South African Pharmacy Council